(untitled) (Sains Humanika, 2022)
Dominant behaviours are displayed when individuals intend to hold power in romantic relationship. Dominant behaviours were proven to affect the level of romantic relationship satisfaction. However, ability-based emotional intelligence which practically can be improved by education or training, play a role in the adjustment of dominant behaviour nature of an individual. The main objective of this study was to determine whether emotional intelligence mediates the relationship between dominant behaviour and romantic relationship satisfaction among UTM married students. This study was cross-sectional in nature and questionnaires were responded 297 married postgraduate UTM students. Data were analysed using descriptive statistics, correlation and regression with the use of SPSS version 26. The mediating effect was determined using Bootstrapping through PROCESS Macro version 3.5.3. The main findings of this study revealed that the emotional intelligence significantly mediates the relationship of dominant behaviour and romantic relationship satisfaction. However, the direct effect of dominant behaviour on romantic relationship satisfaction is greater than the indirect effect of dominant behaviour on romantic relationship satisfaction via emotional intelligence. The implications and recommendations related to this study are also discussed.